Program održivog razvoja Gorskog kotara (University of Maribor Press, 2021)
The Sustainable Development Program of Gorski kotar. The book »The sustainable development program of Gorski kotar« is the result of the project, with which we wanted to stimulate the sustainability and strategic development of the Croatian border area of Gorski kotar all the way from Prezid to Gerovo. The area is distant from the main Croatian roads, but at the same time it is located between three countries (Croatia, Slovenia and Italy), which have always been a source of employment, information and social life for the locals. The intertwining of different traditions enabled the creation of an autochthonous culture that combines interesting stories, customs, crafts, dishes and the use of natural resources from the unspoiled nature in which the destination is located. All of this is an excellent basis for the development of tourism, which can, as a new industry, enable the development of the economy, reverses the demographic picture and stimulates the overall development of the area. The strategic challenge of the tourism development was addressed during two years by tutors and students of the Master’s program Tourism at the Faculty of Tourism University of Maribor together by participatory planning and involvement of local community. After the analysis of the situation, they prepared a development vision, identified the priority areas of work, defined the indicators and the way they would be monitored. The action plan itself is based on the theory of carrying capacity assessment. Monografija „Program održivog razvoja Gorskog kotara“ predstavlja zbirku rezultata projekta s kojim smo željeli promovirati održivo poslovanje i strateški razvoj hrvatskog pograničnog područja Gorskog kotara od Prezida do Gerova. Područje je daleko od glavnih hrvatskih cesta, ali istodobno smješteno između tri države (Hrvatska, Slovenija i Italija), koje su mještanima uvijek bile izvor zaposlenja, informiranja i društvenog života. Ispreplitanje različitih tradicija omogućilo je stvaranje autohtone kulture koja kombinira zanimljive priče, običaje, zanate, jela i upotrebu prirodnih resursa iz netaknute prirode u kojoj leži odredište. Sve je to izvrsna osnova za razvoj turizma, koji kao nova industrija može omogućiti razvoj gospodarstva, preokrenuti demografsku sliku i potaknuti cjelokupni razvoj područja. Tijekom dvije godine mentori i studenti magistarskog programa Turizam na Fakultetu za turizam Sveučilišta u Mariboru razgovarali su o strateškom izazovu razvoja turizma uz participativno sudjelovanje lokalnog stanovništva. Nakon analize stanja pripremili su viziju razvoja i utvrdili prioritetna područja rada, definirali mjere i utvrdili pokazatelje i način njihovog praćenja. Sam akcijski plan temelji se na teoriji procjene nosivosti okoliša.